Silymarin as a functional antioxidant enhances oocyte competence and embryo development in Tharparkar cattle (Bos indicus) - Diksha Upreti; Brijesh Kumar; Meraj Haider Khan; Vikrant Chouhan; Renu Sharma; Vishnu Vadera; Divyanshu Lakhanpal; Pooja Mahala; Meeti Punetha; Shraddha Dwivedi; Anuj Chauhan; Sanjay Kumar Singh (Theriogenology, 2026)

A DREB-like Transcription Factor from Ocimum sanctum L., OscDREB1, Regulates Plant Growth and Confers Abiotic Stress Tolerance in Transgenic Tobacco - Rituraj Kumar; Arpita Singh; Supriya Rana; Vikrant Gupta (Plant Molecular Biology Reporter, 2026)

Analysing expression of cell wall-related and developmental associated genes in mungbean (Vigna radiata (L.) Wilczek) - Shouvik Das; Anant Mohan Sharma; Apurva Gangal; Vikrant Bhati; Gyan Prakash Mishra; Harsh Kumar Dikshit; Prashant Anupama-Mohan Pawar (Plant Physiology Reports, 2026)

Navigating the catalytic landscape for methyl ethyl ketone abatement: A critical review of noble metal versus metal oxide strategies - Kumar Vikrant; Dimitrios A. Giannakoudakis; Tung Nguyen-Dang; Duc-Trung Nguyen; Manh-Huong Phan (Environmental Research, 2026)

Unraveling the genomic structures, conserved functional domains and evolutionary dynamics of beta-defensins in Bubalus bubalis and Ovis aries - Sonam Yadav; Chanchal Rana; Fanny Josan; Mir Ahmad Habib; Aditya Patel; Vikrant Gaur; Rakesh Kumar (Immunogenetics, 2026)

Hydrochemical budgeting of a tropical estuary Vis-à-Vis tidal dynamics: Ecosystem trophic status assessment - Susmita Raulo; Sanjiba Kumar Baliarsingh; Alakes Samanta; Aneesh A. Lotliker; Sudheer Joseph; Sambit Singh; Tamoghna Acharyya; Vikrant V. Patil; T.M. Balakrishnan Nair (Journal of Marine Systems, 2026)

Interfacial charge regulation in acid-treated microporous carbon/titanium dioxide composites for efficient photocatalytic toluene mineralization - Yong-Seong Lee; Kumar Vikrant; Hubdar Ali Maitlo; Ki-Hyun Kim (Chemical Engineering Journal, 2026)

Electrifying catalysis: Joule heating-driven advanced materials for volatile organic compound oxidation - Kumar Vikrant; Yongbiao Hua; Dimitrios A. Giannakoudakis; Quan-Doan Mai; Anh-Tuan Le; Manh-Huong Phan (Chemical Engineering Journal, 2026)

Urban expansion mapping: an analysis of land cover change and sustainability in Delhi using GIS (2000–2025) - Vikrant Pachouri; Jigyasa Parmar; Prafull Kothari; Rajesh Singh; Anita Gehlot; Amit Kumar Thakur; Sudhanshu Dogra (Applied Geomatics, 2026)

Light-to-chemical energy conversion of silver-incorporated manganese dioxide Schottky junction photocatalysts for the photomineralization of hydrogen sulfide - Xueli He; Kumar Vikrant; Wanfeng Yue; Zhansheng Lu; Ki-Hyun Kim (Journal of Cleaner Production, 2026)

Non-methane hydrocarbon (NMHC) variability in rural Himalayan atmospheres: impacts on ozone, secondary organic aerosols, and human health - Mahendar Chand Rajwar; Manish Naja; Prajjwal Rawat; Vikrant Tomar; Mukesh Kumar; Priyanka Srivastava; Shyam Lal (Environmental Science and Pollution Research, 2026)

Sustainable Water Management in Arid Regions: Integrating Technological Innovations and Nature-Based Solutions - Vikrant Pachouri; Prafull Kothari; Rajesh Singh; Anita Gehlot; Amit Kumar Thakur (Water Resources Management, 2026)

Uncovering genetic architecture of powdery mildew resistance in wheat-Aegilops derivatives via multi-locus genome wide association mapping - Imran Sheikh; Shoeb Ahmed; Jitendra Kumar; Vikrant Tyagi; Neeraj Kumar Vasistha; Sushma Sharma; Joy Roy; Harcharan Singh Dhaliwal (Physiological and Molecular Plant Pathology, 2025)

Design, performance, and charge transfer insights into step-scheme zinc hydroxystannate/titanium dioxide heterostructures for enhanced photocatalytic oxidation of gaseous benzene - Yongbiao Hua; Kumar Vikrant; Dae-Hwan Lim; Changqi Chen; Zhansheng Lu; Yan Lu; Ki-Hyun Kim (Journal of Hazardous Materials, 2025)

Associative Genetic Diversity of Theileria Annulata Calf Isolates from Northern India Based on Cyt B Gene - Sanjeev Kumar; Daya Shanker; Vikrant Sudan; Shanker Kumar Singh (Acta Parasitologica, 2025)

Biogenically synthesized Cu2O/MWCNT nanocomposite: Physicochemical properties and application as a green catalyst for visible-light-driven degradation of organic pollutants - Neeraj Mishra; Shikha Gulati; Vikrant Singh Rao; Yamini Moriya; Gunjan Dubey; Sanjay Kumar (Next Research, 2025)

Synthesis, performance, and reaction mechanisms of titanium dioxide-silicon carbide as a step-scheme heterojunction photocatalyst against formaldehyde in air - Xueli He; Kumar Vikrant; Danil W. Boukhvalov; Ki-Hyun Kim (Chemical Engineering Journal, 2025)

Corrigendum to “Evidence of the dominant role of particle size in controlling the dynamic adsorption breakthrough behavior of gaseous benzene in a microporous carbon bed system” [Chem. Eng. J. 427 (2022) 130977] - Seung-Ho Ha; Sherif A. Younis; Kumar Vikrant; Jan E. Szulejko; Ki-Hyun Kim (Chemical Engineering Journal, 2025)

Early Blight Disease Management of Potato - Vikrant Sharma; Amanpreet Kaur; Anil Kumar (Potato Research, 2025)

A review of river sand mining: Methods, impacts, and implications - Indra Mani Tripathi; Shanti Shwarup Mahto; Chandrashekhar Bhagat; Ankit Modi; Vikrant Jain; Pranab Kumar Mohapatra (Next Research, 2025)

Lithological controls on chemical weathering signatures in the semi-arid climatic regime: Study based on tropical small scale catchments - Ravi Kant Prasad; Naman Deep Singh; Sunil Kumar Singh; Vikrant Jain (Geomorphology, 2025)

Factors controlling basalt weathering in the Deccan traps: A small catchment perspective - Ravi Kant Prasad; Naman Deep Singh; Sunil Kumar Singh; Vikrant Jain (CATENA, 2025)

Tuning the metal-support interactions in titanium dioxide-supported palladium photocatalysts against toluene in air - Jinjian Zhang; Kumar Vikrant; Ki-Hyun Kim; Danil W. Boukhvalov; Jan E. Szulejko (Environmental Research, 2024)

Functionalization of psyllium to develop bioactive network hydrogels for sustained drug delivery - Vikrant Sharma; Baljit Singh; Raj Kumar Thakur (Bioactive Carbohydrates and Dietary Fibre, 2024)

Identification and pyramiding of iron and zinc homeostasis genes introgressed from non-progenitor Aegilops species to bread wheat - Harneet Kaur; Vikrant Tyagi; Jitendra Kumar; Joy K Roy; Vishal Chugh; Naseer Ahmed; Harcharan Singh Dhaliwal; Imran Sheikh (Euphytica, 2024)

The catalytic efficacy of modified manganese-cobalt oxides for room-temperature oxidation of formaldehyde in air - Yongbiao Hua; Kumar Vikrant; Ki-Hyun Kim; Philippe M. Heynderickx; Danil W. Boukhvalov (Journal of Hazardous Materials, 2024)

Cold plasma technology: Reshaping food preservation and safety - Samandeep Kaur; Yogesh Kumar; Vikrant Singh; Jasmeen Kaur; Parmjit S. Panesar (Food Control, 2024)

Morphology, chemical composition, and biological activities of Aconitum balfourii: a comprehensive review of important Himalayan and highly exploited medicinal plant - Vikrant Kumar; Rajni Kant Sharma; Sunil K. Singh; Kiran Arora; Mukesh C. Joshi; Preeti Rawat; Madhulika Singh (Vegetos, 2024)

Low-temperature thermocatalytic removal of formaldehyde in air using copper manganite spinels - Yongbiao Hua; Kumar Vikrant; Ki-Hyun Kim; Philippe M. Heynderickx; Danil W. Boukhvalov (Environmental Research, 2024)

Thermocatalytic oxidation potential of cobalt(II,III) oxide against gaseous formaldehyde in relation to hydrothermal synthesis temperature - Yongbiao Hua; Kumar Vikrant; Ki-Hyun Kim; Seunghyun Weon; Danil W. Boukhvalov (Chemical Engineering Journal, 2024)

Development of southern corn leaf blight (SCLB) resistant and high-popping volume composite popcorn using phenotypic and marker-assisted selection (MAS) - Shivani Thakur; Rahul Kumar; Baldeep Singh; Yogesh Vikal; H. S. Dhaliwal; Vikrant Tyagi; Imran Sheikh (Cereal Research Communications, 2024)

Investigation of thermal performance, drying characteristics and environomical analysis: direct flow evacuated tube solar drying of okra - Dhiraj Kumar Yadav; Vinkel Kumar Arora; Vikrant Yadav (Environmental Science and Pollution Research, 2024)

Titanium dioxide–supported mercury photocatalysts for oxidative removal of hydrogen sulfide from the air using a portable air purification unit - Shaoqing Sun; Kumar Vikrant; Ki-Hyun Kim; Danil W. Boukhvalov (Journal of Hazardous Materials, 2024)

Dominance of soil moisture over aridity in explaining vegetation greenness across global drylands - Indra Mani Tripathi; Shanti Shwarup Mahto; Anuj Prakash Kushwaha; Rahul Kumar; Amar Deep Tiwari; Bidhan Kumar Sahu; Vikrant Jain; Pranab Kumar Mohapatra (Science of The Total Environment, 2024)

Thermocatalytic oxidation of a binary mixture of formaldehyde and toluene at ambient levels by a titanium dioxide supported platinum catalyst - Hyejin Shin; Kumar Vikrant; Ki-Hyun Kim; Philippe M. Heynderickx; Danil W. Boukhvalov (Science of The Total Environment, 2024)

Low-temperature oxidative removal of benzene from the air using titanium carbide (MXene)-Supported platinum catalysts - Jiapeng Wang; Kumar Vikrant; Sherif A. Younis; Ki-Hyun Kim; Philippe M. Heynderickx (Chemosphere, 2024)

Gas-phase hydrogenation of furfural into value-added chemicals: The critical role of metal-based catalysts - Kumar Vikrant; Ki-Hyun Kim (Science of The Total Environment, 2023)

CRISPR/Cas mediated disruption of BMPR-1B gene and introduction of FecB mutation into the Caprine embryos using Easi-CRISPR strategy - Bosco Jose; Meeti Punetha; Manoj Kumar Tripathi; Shivani Khanna; Vijay Yadav; Amit Kumar Singh; Brijesh Kumar; Kiranjeet Singh; Vikrant Singh Chouhan; Mihir Sarkar (Theriogenology, 2023)

A platinum ensemble catalyst for room-temperature removal of formaldehyde in the air - Kumar Vikrant; Myoung Won Chung; Danil W. Boukhvalov; Philippe M. Heynderickx; Ki-Hyun Kim; Seunghyun Weon (Chemical Engineering Journal, 2023)

Genetic analysis of iron, zinc and grain yield in wheat-Aegilops derivatives using multi-locus GWAS - Harneet Kaur; Prachi Sharma; Jitendra Kumar; Vikas Kumar Singh; Neeraj Kumar Vasistha; Vijay Gahlaut; Vikrant Tyagi; Shailender Kumar Verma; Sukhwinder Singh; H S Dhaliwal; Imran Sheikh (Molecular Biology Reports, 2023)

Multimerin 1 aids in the progression of ovarian cancer possibly via modulation of DNA damage response and repair pathways - Abhinav Saini; Vikrant Kumar; Anil Kumar Tomar; Alpana Sharma; Savita Yadav (Molecular and Cellular Biochemistry, 2023)

Performance validation of a non-photocatalytic air purifier built by reactive adsorbent against a commercial UV-based air purifier - Won-Ki Kim; Jeong-Min Kim; Kumar Vikrant; Ki-Hyun Kim (Chemical Engineering Journal, 2023)

Metal oxide/activated carbon composites for the reactive adsorption and catalytic oxidation of formaldehyde and toluene in air - Won-Ki Kim; Kumar Vikrant; Sherif A. Younis; Ki-Hyun Kim; Philippe M. Heynderickx (Journal of Cleaner Production, 2023)

Architecting the Z-scheme heterojunction of Gd2O3/g-C3N4 nanocomposites for enhanced visible-light-induced photoactivity towards organic pollutants degradation - Vikrant Singh Rao; Rishabh Sharma; Devina Rattan Paul; Miroslav Almáši; Anshu Sharma; Suresh Kumar; Satya Pal Nehra (Environmental Science and Pollution Research, 2023)

Recent trends and applications of evacuated tube solar collector in food processing and air heating: a review - Santanu Malakar; Vinkel Kumar Arora; Prabhat K. Nema; Vikrant Yadav (Environmental Science and Pollution Research, 2023)

Photocatalytic removal of organic dye using green synthesized zinc oxide coupled cadmium tungstate nanocomposite under natural solar light irradiation - Bushra Fatima; Sharf Ilahi Siddiqui; Hament Kumar Rajor; Maqsood Ahmad Malik; Katabathini Narasimharao; Rabia Ahmad; Kumar Vikrant; Taejin Kim; Ki-Hyun Kim (Environmental Research, 2023)

Assessment of Late Blight Resistance in Indian Potato Cultivars and Associated Biochemical Changes During Disease Development - Amanpreet Kaur; Vikrant Sharma; Anil Kumar (Potato Research, 2022)

Filgrastim, a Recombinant Form of Granulocyte Colony-stimulating Factor, Ameliorates 3-nitropropionic Acid and Haloperidol-induced Striatal Neurotoxicity in Rats - Vikrant Rahi; Parladh Ram; Puneet Kumar (Neurotoxicity Research, 2022)

IL-3 inhibits rat osteoclast differentiation induced by TNF-α and other pro-osteoclastogenic cytokines - Vikrant Piprode; Kanupriya Singh; Anil Kumar; Snehal R. Joshi; Mohan R. Wani (Journal of Biosciences, 2021)

Synthesis of highly fluorescent and water soluble graphene quantum dots for detection of heavy metal ions in aqueous media - Savan K. Raj; Vikrant Yadav; Gopala R Bhadu; Rajesh Patidar; Manoj Kumar; Vaibhav Kulshrestha (Environmental Science and Pollution Research, 2021)

Role of vitamins and minerals as immunity boosters in COVID-19 - Puneet Kumar; Mandeep Kumar; Onkar Bedi; Manisha Gupta; Sachin Kumar; Gagandeep Jaiswal; Vikrant Rahi; Narhari Gangaram Yedke; Anjali Bijalwan; Shubham Sharma; Sumit Jamwal (Inflammopharmacology, 2021)

Larger floods of Himalayan foothill rivers sustained flows in the Ghaggar–Hakra channel during Harappan age - Ajit Singh; Vikrant Jain; Michel Danino; Naveen Chauhan; Rahul Kumar Kaushal; Shantamoy Guha; V. N. Prabhakar (Journal of Quaternary Science, 2021)
The human–landform interaction in the region of the Ghaggar–Hakra palaeochannel in the northwest Indo‐Gangetic plains during the Bronze Age Indus/Harappan civilisation (~4.6–3.9 thousand years before the present, ka bp ) remains an enigmatic case due to a paucity of evidence regarding the hydrology of the then existing river. Here, we estimated the palaeohydrology of the foothill Markanda River in the sub‐Himalayan catchment of the Ghaggar–Hakra (G–H) palaeochannel. Our morphology and chronology results show aggradation of a fan (57.7 ka) during the Late Pleistocene and T–1 to T–5 fluvial terraces (13.1 to 6.0 ka) during the terminal Pleistocene to Holocene, and deposition of palaeoflood sediments (3.9–3.8 ka) over the T–3 terraces during the Late Holocene. Considering the known uplift rates along the Himalayan frontal thrust, and our estimated aggradation rates, we derived channel palaeogeometry and calculated peak discharge at the site of palaeoflood deposits. We conclude that the Markanda River's peak discharge was several orders of magnitude higher during the Late Holocene than the modern‐day peak discharge of 100‐year return period. The palaeoflood deposits represent larger flooding of the foothill rivers that sustained flows in the downstream reaches of the Ghaggar–Hakra palaeochannel during the Late Harappan civilisation.

Analysis of Multimerin 1 (MMRN1) expression in ovarian cancer - Abhinav Saini; Kumari Binita Chandra; Vikrant Kumar; Sandeep R Mathur; J B Sharma; Sunesh Kumar; Savita Yadav (Molecular Biology Reports, 2020)

Sediment and Submarine Groundwater Discharge Mediated Arsenic Flux into the Bay of Bengal, India: an Appraisal - Anant Misra; Ashwin Singh; D. S. Suresh Babu; Vikrant Jain; Mithila Verma; Brijesh K. Bansal; Manish Kumar (Current Pollution Reports, 2020)

Protective Effect of Hemin Against Experimental Chronic Fatigue Syndrome in Mice: Possible Role of Neurotransmitters - Vandana Thakur; Sumit Jamwal; Mandeep Kumar; Vikrant Rahi; Puneet Kumar (Neurotoxicity Research, 2020)

Sugarcane and Wheat Productivity Under Different Cropping Systems - Kuldeep Singh; Sudhir Kumar Mishra; Vikrant Singh (Sugar Tech, 2019)

First report of molecular characterization and sequence phylogenetic analysis of Linguatula serrata from India - Vikrant Sudan; Daya Shanker; Amit Kumar Jaiswal (Acta Parasitologica, 2018)
Linguatula serrata is a pentastomid which is worldwide in distribution. However, a very few references are reported from India. In the present study, the cox I gene of L. serrata nymphs, originally isolated from mesenteric lymph nodes of buffaloes, was amplified and custom sequenced. Based on sequence analysis, two haplotypes were noticed and were subsequently submitted in NCBI database. The sequences were also compared with the other sequences available in the pubmed and phylogenetic analysis coupled with nucleotide homologies were commutated. The studied Indian isolates were found closer to Bangladesh and Iran isolates. This is the first report of molecular characterization of L. serrata from India.

Variation in cardiac markers and electrocardiographic alterations in young calves naturally infected with bovine tropical theileriosis - Kapil Kumar Gupta; Mukesh Srivastava; Vikrant Sudan; Shanker Kumar Singh; Soumen Choudhury; Daya Shanker (Tropical Animal Health and Production, 2018)

Piperazine clubbed with 2-azetidinone derivatives suppresses proliferation, migration and induces apoptosis in human cervical cancer HeLa cells through oxidative stress mediated intrinsic mitochondrial pathway - Rashmin Khanam; Raj Kumar; Iram Iqbal Hejazi; Syed Shahabuddin; Ramovatar Meena; Vikrant Jayant; Prabhat Kumar; Abdul Roouf Bhat; Fareeda Athar (Apoptosis, 2018)

First report of molecular characterization and phylogenetic analysis of RoTat 1.2 VSG of Trypanosoma evansi from equine isolate - Vikrant Sudan; Amit Kumar Jaiswal; Daya Shanker; Amit Kumar Verma (Tropical Animal Health and Production, 2017)

Expression analysis of NOS family and HSP genes during thermal stress in goat (Capra hircus) - Vijay Pratap Yadav; Satyaveer Singh Dangi; Vikrant Singh Chouhan; Mahesh Gupta; Saroj K. Dangi; Gyanendra Singh; Vijay Prakash Maurya; Puneet Kumar; Mihir Sarkar (International Journal of Biometeorology, 2016)

First molecular evidence of the transplacental transmission of Theileria annulata - Vikrant Sudan; Shanker Kumar Singh; Amit Kumar Jaiswal; Rahul Parashar; Daya Shanker (Tropical Animal Health and Production, 2015)

Expression of HSPs: an adaptive mechanism during long-term heat stress in goats (Capra hircus) - Satyaveer Singh Dangi; Mahesh Gupta; Saroj K. Dangi; Vikrant Singh Chouhan; V. P. Maurya; Puneet Kumar; Gyanendra Singh; Mihir Sarkar (International Journal of Biometeorology, 2015)

A duplex PCR-based assay for simultaneous detection of Trypanosoma evansi and Theileria annulata infections in water buffaloes - Vikrant Sudan; Amit Kumar Jaiswal; Rahul Parashar; Daya Shanker (Tropical Animal Health and Production, 2015)

Detection of antibodies to Toxoplasma gondii in domesticated ruminants by recombinant truncated SAG2 enzyme-linked immunosorbent assay - Harkirat Singh; Anup Kumar Tewari; Ashok Kumar Mishra; Biswaranjan Maharana; Vikrant Sudan; Opinder Krishan Raina; Jammi Raghavendra Rao (Tropical Animal Health and Production, 2015)

Quantitative structure–activity relationship (QSAR) studies as strategic approach in drug discovery - Harun M. Patel; Malleshappa N. Noolvi; Poonam Sharma; Varun Jaiswal; Sumit Bansal; Sandeep Lohan; Suthar Sharad Kumar; Vikrant Abbot; Saurabh Dhiman; Varun Bhardwaj (Medicinal Chemistry Research, 2014)

Impact of short-term heat stress on physiological responses and expression profile of HSPs in Barbari goats - Satyaveer Singh Dangi; Mahesh Gupta; Vimla Nagar; Vijay Pratap Yadav; Saroj K. Dangi; Om Shankar; Vikrant Singh Chouhan; Puneet Kumar; Gyanendra Singh; Mihir Sarkar (International Journal of Biometeorology, 2014)

Tissue specific response of Agrobacterium tumefaciens attachment to Sorghum bicolor (L) Moench - Anju Verma; Vikrant Nain; Chetana Kumari; Santosh Kumar Singh; M. Lakshmi Narasu; P. Ananda Kumar (Physiology and Molecular Biology of Plants, 2008)

Polymerase chain reaction analysis of transgenic plants contaminated byAgrobacterium - Vikrant Nain; Rajani Jaiswal; Monika Dalal; Bandarupalli Ramesh; Polumetla A. Kumar (Plant Molecular Biology Reporter, 2005)

Sequence analysis of the long arm of rice chromosome 11 for rice?wheat synteny - Saurabh Raghuvanshi; Subodh K. Srivastava; Anupama Gaur; Ajit K. Pal; Vivek Dalal; Archana Singh; Irfan A. Ghazi; Ashutosh Bhargav; Mahavir Yadav; Anupam Dixit; Kamlesh Batra; Kishor Gaikwad; et al. (Functional & Integrative Genomics, 2004)

Structural and functional analysis of rice genome - Akhilesh K. Tyagi; Jitendra P. Khurana; Paramjit Khurana; Saurabh Raghuvanshi; Anupama Gaur; Anita Kapur; Vikrant Gupta; Dibyendu Kumar; V. Ravi; Shubha Vij; Parul Khurana; Sulabha Sharma (Journal of Genetics, 2004)

Status of Austro-Asiatic groups in the peopling of India: An exploratory study based on the available prehistoric, linguistic and biological evidences - Vikrant Kumar; B. Mohan Reddy (Journal of Biosciences, 2003)